2011
DOI: 10.1108/13552511111116259
|View full text |Cite
|
Sign up to set email alerts
|

Cost of poor maintenance

Abstract: Purpose -The purpose of this paper is to propose and discuss cost of poor maintenance (CoPM), as a concept for managing the improvement of maintenance performance within manufacturing industry. Design/methodology/approach -The paper is based on literature studies and two workshops with representatives from industry and academia. Findings -CoPM is proposed as a new concept for maintenance performance improvement. The concept is derived from established practices in quality costing and hence it should be easily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(22 citation statements)
references
References 19 publications
(18 reference statements)
0
18
0
4
Order By: Relevance
“…Dalam sebuah industri, perawatan merupakan aktivitas yang tidak dapat dihindari, yang tentunya membutuhkan biaya dalam melaksanakan kegiatan perawatan. Dari total biaya produksi dalam sebuah industry, rata-rata diatas 15 % alokasi biaya untuk perawatan, biaya tersebut dapat menjadi tinggi dikarenakan penambahan biaya karena tidak adanya rencana perawatan atau perawatan preventif yang kurang baik sehingga akan menyebabkan total biaya produksi menjadi naik [10]. Perencanakan perawatan bagi sebuah system, perlu diidentifikasi komponen pada system tersebut yang dapat menyebabkan kegagalan system, bagaimana moda kegagalannya dan apa akibat yang ditimbulkan dari kegagalan tersebut.…”
Section: Latar Belakangunclassified
See 2 more Smart Citations
“…Dalam sebuah industri, perawatan merupakan aktivitas yang tidak dapat dihindari, yang tentunya membutuhkan biaya dalam melaksanakan kegiatan perawatan. Dari total biaya produksi dalam sebuah industry, rata-rata diatas 15 % alokasi biaya untuk perawatan, biaya tersebut dapat menjadi tinggi dikarenakan penambahan biaya karena tidak adanya rencana perawatan atau perawatan preventif yang kurang baik sehingga akan menyebabkan total biaya produksi menjadi naik [10]. Perencanakan perawatan bagi sebuah system, perlu diidentifikasi komponen pada system tersebut yang dapat menyebabkan kegagalan system, bagaimana moda kegagalannya dan apa akibat yang ditimbulkan dari kegagalan tersebut.…”
Section: Latar Belakangunclassified
“…Dalam penilaian RPN, nilai yang ditetapkan pada tiga index skala kualitatif ditafsirkan sebagai angka. Informasi dikumpulan dengan skala kualitatif dan dan digunakan pada skala kuantitatif dengan sifat yang berbeda dari yang pertama [10].…”
Section: Gambar 1 Flow Chart Metode Penilaian Risiko Dengan Pendekataunclassified
See 1 more Smart Citation
“…Studies have demonstrated few problems had arisen as the resources budgeted by the management are deficient as it unable to support the maintenance programs and have caused cost overruns. The low budget and cost overruns will result in lower building performance and increased risk of poor management of a building (Ali, Kamaruzzaman, Sulaiman, & Cheong Peng, 2010; Au-Yong, Ali, & Ahmad, 2014a; Salonen & Deleryd, 2011). It is necessary to unveil the real practice of the maintenance budgeting to determine the causes of ill-budgeted of maintenance resources.…”
Section: Introductionmentioning
confidence: 99%
“…Although maintenance function is important to support manufacturing system, it is often considered as a cost centre rather than a competitive advantage [4]. Commonly, the annual cost of maintenance runs between 7-15 % of the investment [3].…”
Section: Introductionmentioning
confidence: 99%